A review of sustainable solar irrigation systems for Sub-Saharan Africa - Wazed, Saeed Mohammed; Hughes, Ben Richard; O'Connor, Dominic; Calautit, John Kaiser (Elsevier, 2018)
This investigation focused on the research undertaken on solar photovoltaic (PV) and solar thermal technologies for pumping water generally for irrigation of remote rural farms specifically considering the Sub-Saharan African region. Solar PV systems have been researched extensively for irrigation purposes due to the rise in Oil prices and the upscaling in commercialisation of PV technology. Based on the literature the most effective PV system is presented for the irrigation of a small scare remote rural farm with respect to the cost, pumping capacity and system efficiency. Similarly, solar thermal systems are reviewed and the most effective system described. Unlike PV technology, solar thermal technology for water pumping is lacking especially in small scale operations. However, with the possibility of local production, low investment cost, easy maintenance and lower carbon footprint, solar thermal water pumping technologies may be able to overcome the shortcomings of the PV technology that has stopped widespread use of the technology for irrigation applications. Taking into consideration recent developments in concentrated solar technologies using the Stirling engine, novel solar thermal water pumping systems may be developed. This review also highlighted the different methodologies such as modelling, used to investigate and optimise the performance of solar powered systems.